Depositional environment and provenance of the upper Permian–Lower Triassic Tianquanshan Formation, northern Tibet: implications for the Palaeozoic evolution of the Southern Qiangtang, Lhasa, and Himalayan terranes in the Tibetan Plateau. Issue 2 (25th January 2016) - Fan, Jian-Jun; Li, Cai; Xie, Chao-Ming; Liu, Yi-Ming
Abstract: This article reports the depositional environment and provenance for the Tianquanshan Formation in the Longmuco–Shuanghu–Lancangjiang suture zone, and uses these to better understand the tectonic evolution of this region. Zircons in the andesite of the Tianquanshan Formation yielded concordia ages of 246, 247, and 254 Ma, indicating that the Tianquanshan Formation formed during the late Permian–Early Triassic. The Tianquanshan Formation consists of flysch and ocean island rock assemblages, indicating that the Longmuco–Shuanghu–Lancangjiang Palaeo-Tethys Ocean continued to exist as a mature ocean in the late Permian–Early Triassic. The detrital zircons in the greywackes of the Tianquanshan Formation yielded peak ages of 470–620, 710–830, 910–1080, 1450–1660, and 2400–2650 Ma, indicating the provenance of the Tianquanshan Formation was either Indian Gondwana or terranes that have an affinity with Indian Gondwana in the Tibetan Plateau (i.e. the Southern Qiangtang, Lhasa, and Himalayan terranes). The Ordovician quartzites, Carboniferous sandstones, Carboniferous–Permian diamictites, and the Upper Permian–Lower Triassic greywackes in the Southern Qiangtang, Lhasa, and Himalayan terranes all contain detrital zircons with youngest ages of ca. 470 Ma, indicating their source areas have been in a stable tectonic environment since the Ordovician, and this inference is supported by the continuous deposition in a littoral–neritic passive margin in these regions from the Ordovician to the lower Permian. Combining the present results with regional geological data, we infer that the Southern Qiangtang, Lhasa, and Himalayan terranes were all in a stable passive continental margin along the northern part of Indian Gondwana during the long period from the Ordovician to the early Permian. At early Permian, because of the opening of the Neo-Tethys Ocean, the tectonic framework of this region underwent a marked change to a rifting and active environment.